2008
DOI: 10.2478/v10001-008-0020-1
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Irritation After Inhalation Exposure to Benzalkonium Chloride in Rats

Abstract: Background: Benzalkonium chloride (BAC) is a quaternary ammonium compound (QAC) with a C 8 to C 18 chain length of alkyl groups. Since BAC exerts toxic effects on microorganisms, it has been used as an effective germicide and preservative, mostly in cosmetic industry and medicine. However, the toxic potential of BAC may be hazardous to humans, due to the common use of preparations containing BAC as a preservative. Material and Methods: To assess the possible toxic effects of BAC, two-stage experiments were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…In an inhalation study performed in mice, it was found that inhalation of BAC at higher concentrations induced deep lung effects and also lung inflammation [25]. In previous years we assessed toxic effects of BAC to the respiratory system and changes in the concentrations of catecholamines in the brain of rats exposed by inhalation to BAC aerosol [26,27]. The present study is an extension of our earlier works assessing the toxic effects of exposure to aerosol of BAC water solution in laboratory animals under conditions of repeated inhalation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In an inhalation study performed in mice, it was found that inhalation of BAC at higher concentrations induced deep lung effects and also lung inflammation [25]. In previous years we assessed toxic effects of BAC to the respiratory system and changes in the concentrations of catecholamines in the brain of rats exposed by inhalation to BAC aerosol [26,27]. The present study is an extension of our earlier works assessing the toxic effects of exposure to aerosol of BAC water solution in laboratory animals under conditions of repeated inhalation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings in the present study indicated that topically applying DDAC to the lung alters lung antioxidant and antimicrobial defense systems, amplifying inflammatory responses by systemic administration of an exogenous stimulus, LPS. One of the QACs, BAC, induced pulmonary injury after inhalation (Swiercz et al, 2008) or oral administration (mediated by aspiration of a small amount into the bronchi) (Xue et al, 2004) in rats. These data, however, did not demonstrate the precise toxic effects on respiratory systems by QAC.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Data also suggest toxic effects of phenylcarbinol, another common preservative. [11][12][13] Despite the evidence showing that benzalkonium chloride and other preservatives can be damaging to human and animal tissues, preservatives are in widespread use in overthe-counter and prescription preparations.…”
Section: Discussionmentioning
confidence: 99%